Female Sexuality and its Repression in a Postcolonial Situation: A Critical Analysis of the Portrayal of Women’s Position Within Patriarchy in Deepa Mehta’s Fire (1996) - Tahsin, Jeba (Journal of Journalism and Media, 2024)
Deepa Mehta’s 1996 film, Fire sparked controversy for its portrayal of lesbian love between two women trapped in a loveless marriage within a patriarchal society. This research deals with the film as a critical analysis of how female sexuality is repressed in a postcolonial context. The focus will be on Mehta’s portrayal of the protagonists, Sita and Radha and how their desires are stifled by the confines of their marriage to a shared, emotionally distant husband. The analysis will explore how their unconventional relationship becomes a form of rebellion against societal norms and the patriarchal structures that dictate female behavior and sexuality. Fire’s portrayal of female desire and intimacy will be examined to understand how it challenges the traditional heterosexual framework and the power dynamics within it. The research will also consider the film’s reception and the controversies it ignited, exploring how it challenged social and cultural taboos surrounding female sexuality in a postcolonial nation.